2018
DOI: 10.3171/2017.4.jns163195
|View full text |Cite
|
Sign up to set email alerts
|

The V3 segment of the vertebral artery as a robust donor for intracranial-to-intracranial interpositional bypasses: technique and application in 5 patients

Abstract: The V segment of the vertebral artery (VA) has been studied in various clinical scenarios, such as in tumors of the craniovertebral junction and dissecting aneurysms. However, its use as a donor artery in cerebral revascularization procedures has not been extensively studied. In this report, the authors summarize their clinical experience in cerebral revascularization procedures using the V segment as a donor. A brief anatomical description of the relevant techniques is also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Rennert et al 18 demonstrated functional improvement in 3 patients who underwent superficial temporal artery to SCA bypass for vertebrobasilar artery insufficiency. Meybodi et al 19 and Gandhi et al 20 described alternative technical approaches to posterior circulation bypass using the V3 segment as a donor vessel and the common carotid artery as a recipient vessel, respectively. Britz et al 21 detailed the successful application of radial artery interposition grafting in 3 symptomatic patients with vertebrobasilar ischemia refractory to maximal medical management.…”
Section: Discussionmentioning
confidence: 99%
“…Rennert et al 18 demonstrated functional improvement in 3 patients who underwent superficial temporal artery to SCA bypass for vertebrobasilar artery insufficiency. Meybodi et al 19 and Gandhi et al 20 described alternative technical approaches to posterior circulation bypass using the V3 segment as a donor vessel and the common carotid artery as a recipient vessel, respectively. Britz et al 21 detailed the successful application of radial artery interposition grafting in 3 symptomatic patients with vertebrobasilar ischemia refractory to maximal medical management.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In this report, we used petrous ICA to revascularize UPC in practice for the first time, endowed this novel skull base bypass modality with the benefit of intracranialintracranial bypass 19 for the protection of graft conduits, and shortened the graft length to prevent turbulent flow and artery graft vasospasm to improve the patency rate and maintain the high pressure of blood flow with reduced graft resistance (Figure 3). 20,21 In particular, petrous ICA affords the most robust blood flow resource near the skull base because its diameter is approximately 5 mm, which is equivalent to the external carotid artery (ECA). 22 The Treatment of Basilar Trunk Aneurysms Deserves Utmost High-Flow Bypass High-Flow Bypass for Application of the Flow Reversal Strategy…”
Section: Discussion Skull Base Bypass Affords High-flow Capacitymentioning
confidence: 99%
“…31 This strategy also justified its efficacy in the treatment of dolichoectatic basilar trunk aneurysms. 21,[32][33][34][35] Nevertheless, it is difficult to predict successful conditions, whereas Kalani and Spetzler 10 reported that more than 1/3 of cases exhibited aneurysm enlargement in their series. In our experience, this unfavorable result rests on the employment of superficial temporal artery bypass to either the PCA or superior cerebellar artery (SCA).…”
Section: Discussion Skull Base Bypass Affords High-flow Capacitymentioning
confidence: 99%
“…30 This triangle (usually exposed via a farlateral approach) is used for the surgical exposure of the suboccipital (V 3 ) segment of the VA when the V 3 segment is being considered as a donor or recipient for a bypass procedure. 37,46 In contrast, the subatlantic triangle is located inferolateral to the suboccipital triangle (i.e., inferior and lateral to C-1 and inferior oblique muscle). Surgical exploration of this triangle leads us to the most superior portion of the V 2 VA (atlantoaxial VA), which could be used as a donor or recipient in various craniovertebral junction of posterior fossa pathologies (Table 1).…”
Section: Subatlantic Triangle Versus Suboccipital Trianglementioning
confidence: 99%